2015
DOI: 10.1002/hec.3283
|View full text |Cite
|
Sign up to set email alerts
|

Medical Malpractice Damage Caps and Provider Reimbursement

Abstract: A common state legislative maneuver to combat rising healthcare costs is to reform the tort system by implementing caps on noneconomic damages awardable in medical malpractice cases. Using the implementation of caps in several states and large database of private insurance claims, I estimate the effect of damage caps on the amount providers charge to insurance companies as well as the amount that insurance companies reimburse providers for medical services. The amount providers charge insurers is unresponsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Medical disputes can be resolved through litigation [15,16] or, where alternative dispute resolution (ADR) methods exist, through mediation or arbitration [17,18]. Facing the scarcity of both medical and legal resources, China has advocated mediation as an ADR approach to deal with medical disputes.…”
Section: Introductionmentioning
confidence: 99%
“…Medical disputes can be resolved through litigation [15,16] or, where alternative dispute resolution (ADR) methods exist, through mediation or arbitration [17,18]. Facing the scarcity of both medical and legal resources, China has advocated mediation as an ADR approach to deal with medical disputes.…”
Section: Introductionmentioning
confidence: 99%
“…Avraham et al [ 26 ] found, for example, that some tort reforms reduced insurance premiums, but only for employer-sponsored plans rather than capitated HMO plans [ 26 ]. Friedson [ 27 ] concluded that caps on noneconomic damages reduced insurance reimbursements for certain procedures, but providers did not reduce charges to insurers . Thorpe [ 28 ] reported that state with caps on malpractice claims had insurance premiums that were 17.1% lower than states without caps.…”
mentioning
confidence: 99%
“…Researchers have used Fair Health data to study the effects of medical malpractice damage caps on provider reimbursement (34), market power and provider consolidation (54), the effects of occupational licensing on health care prices (53), the effects of health coverage mandates on provider reimbursement (35), and the opioid crisis among the privately insured (28).…”
Section: New Aggregate Health Care Claims Datamentioning
confidence: 99%